Knowledge management in emerging economies : social, organizational and cultural implementation - Al-Shammari, Minwir, 1962- (Hershey, PA : Information Science Reference, 2011)
'This book focuses on knowledge management theoretical models and empirical research findings for developing economies to create an understanding of the social, organizational, and cultural implementation aspects of knowledge management in the context of developing economies'--Provided by publisher.
Includes bibliographical references (p.. 347-385) and index.
Keywords: Knowledge management -- Developing countries